Study of ATLAS sensitivity to asymmetries in single top events - Fiolhais, Miguel Castro Nunes (2008)
The study of the LHC ATLAS experiment sensitivity to angular and spin asymmetries in the production of single top quarks (t-channel) events was done using the fast detector simulation (ATLFAST) and all the events were generated using Pythia and TopReX libraries. In order to get an efficient selection of events, a likelihood-based analysis was developed for a luminosity of 10 fb-1. From the measurement of these asymmetries, the limits at 68:3% confidence level on the anomalous couplings of the Wtb vertex were set using the TopFit library.